2018
DOI: 10.1021/acs.analchem.8b05260
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating π Interactions by Constructing Concave/Convex Surfaces Using a Bucky Bowl Molecule, Corannulene in Liquid Chromatography

Abstract: Convex–concave π conjugated surfaces in hemispherical bucky bowl such as corannulene (Crn) have shown increasing utility in constructing self-assembled new functional materials owing to its unique π electrons and strong dipole. Here, we investigate these specific molecular recognitions on Crn by developing new silica-monolithic capillary columns modified with Crn and evaluating their performance in the separation of different aromatic compounds by liquid chromatography (LC). We synthesized two Crn derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Interestingly, the Glcs were still separated due to the increase of the glucose unit in both columns. Here, according to our previous studies, fullerenes effectively allowed π interactions, such as the CH-π and/or OH-π interactions 41,42,46 . For this comparison, the measurements were conducted for non-labelled saccharides with the applied columns and the results showed that the separation was achieved for using C60/C70 columns, but not for using C18 columns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the Glcs were still separated due to the increase of the glucose unit in both columns. Here, according to our previous studies, fullerenes effectively allowed π interactions, such as the CH-π and/or OH-π interactions 41,42,46 . For this comparison, the measurements were conducted for non-labelled saccharides with the applied columns and the results showed that the separation was achieved for using C60/C70 columns, but not for using C18 columns.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we successfully prepared C 60 - or C 70 -fullerene (C60, C70) bonded separation media using a silica monolithic capillary and a thermo-reactive agent, perfluorophenyl azide. Then, the specific π interactions were identified for spherical recognition 37 40 , CH–π interaction 41 , 42 , and halogen–π interaction 43 , 44 . According to these effective intermolecular recognitions, we anticipated that the fullerene-bonded separation media might be useful for the separation of saccharides via the CH– or OH–π interaction as well as dipole interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Using various silane reagents is a straightforward way to modify silica monoliths . For example, a corannulene‐immobilized silica monolith was fabricated and applied in the analysis of aromatic analytes by cLC, indicating that the concave surface of corannulene has strong CH‐π interaction with a planar molecule (coronene) . Similarly, a silica monolithic column was modified by a self‐synthesized phosphonium‐based ionic liquid via 3‐(trimethoxysilyl)propyl methacrylate (γ‐MAPS), which was then used for separation of pyrimidine bases and nucleosides in HILIC and exhibited high efficiencies ranging from 98 000 to 174 000 plates m −1 …”
Section: Basic Strategy For Designing Monolithic Materialsmentioning
confidence: 99%
“…39,40 In our previous studies, we developed novel separation media immobilized with carbon materials. [41][42][43] These media exhibited strong p interactions because of their many p electrons. Characteristics of weak interactions from aromatic rings were claried by evaluating their retention behaviors with HPLC measurements.…”
Section: Introductionmentioning
confidence: 99%